Cyclopiazonic acid biosynthesis gene cluster gene cpaM is required for speradine A biosynthesis. Issue 12 (2nd December 2015) - Tokuoka, Masafumi; Kikuchi, Tomoki; Shinohara, Yasutomo; Koyama, Akifumi; Iio, Shin-ichiro; Kubota, Takaaki; Kobayashi, Jun'ichi; Koyama, Yasuji; Totsuka, Akira; Shindo, Hitoshi; Sato, Kazuo
Abstract: Speradine A is a derivative of cyclopiazonic acid (CPA) found in culture of an Aspergillus tamarii isolate. Heterologous expression of a predicted methyltransferase gene, cpaM, in the cpa biosynthesis gene cluster of A. tamarii resulted in the speradine A production in a 2-oxoCPA producing A. oryzae strain, indicating cpaM is involved in the speradine A biosynthesis.